IMPLEMENTASI MEDIA BELAJAR GAMBAR PADA MATA PELAJARAN AL ISLAM ASPEK TARIKH DALAM UPAYA MENINGKATKAN PEMAHAMAN SISWA SMK MUHAMMADIYAH 03 WELERI - Dinar Syifaul Firdaus; Ikhsan Intizam (As-Sulthan Journal of Education, 2025)
This study aims to examine the implementation of image learning media in the subject of Al Islam in the Tarikh aspect as an effort to improve students' understanding at SMK Muhammadiyah 03 Weleri. The background of this study is based on the low interest and understanding of students in Islamic history material due to monotonous and uninteresting lecture methods. By using a qualitative approach through the case study method, data were obtained from direct observation and interviews with teachers and students. The results of the study showed that the use of image media had a positive impact on several aspects of learning, including: increasing the effectiveness of class mastery, fostering student learning motivation, deepening understanding of the material, and creating an interactive and enjoyable learning atmosphere. Referring to Edgar Dale's Cone of Experience theory, it is proven that visual media can significantly increase students' absorption. Therefore, image media can be used as an alternative effective and relevant learning strategy in improving the quality of education, especially in Islamic history material at the vocational high school level.